Utilization of health care services among the elderly population in Gorkha municipility. - Neupane,Sobita (2015)
ABSTRACT: Background: Population aging is a common problem faced in many countries world wide. Due to physiological and biochemical changes in the elderly people, increased incidence of diseases is observed. Methodology: A descriptive Cross-sectional study was conducted. A community-based cross- sectional study was carried out by house to house survey of all people aged over 60 years and above. Information were collected by face to face interview method. Non probability purposive sampling was employed to select the elderly and appropriate statistical tests were used where required. Results :A sample size of 124 was calculated considering prevalence of utilization of health care services. Male respondents were 53.1% whereas female respondents were 46.8%. Among the respondents,71.8 % elderly had visited a hospital for treatment during last one year. Common ailments included Musculoskeletal problem 34.1%, Respiratory problem 28.2%, Gastro intestinal disorder 24.7% .Most of the respondent's chronic problem were Hypertension 24.2% followed by Asthma 20.2% . Most of the respondents recently took medication for digestive disorder 66.7% followed by cardio vascular disorder 30.6%. There is a significant association between utilization of health service and sex. Male respondents utilized more health services than female respondents. Conclusion: Based on study findings, it is concluded that minimum 10.5% utilization of health care services so informal education targeting the senior citizens and awareness programmed focused on health conditions and services available to elderly people are highly recommended. Key Words: Health care services, Utilization, Elderly people, Hospital